Endovascular therapy versus no endovascular therapy in patients receiving best medical management for acute isolated occlusion of the posterior cerebral artery: A systematic review and meta‐analysis. (17th June 2022) - Berberich, Anne; Finitsis, Stephanos; Strambo, Davide; Michel, Patrik; Herweh, Christian; Meyer, Lukas; Hanning, Uta; Strbian, Daniel; Abdalkader, Mohamad; Nogueira, Raul G.; Puetz, Volker; Kaiser, Daniel P. O.; et al.
Abstract: Background and purpose: Endovascular therapy (EVT) is increasingly reported for treatment of isolated posterior cerebral artery (PCA) occlusions although its clinical benefit remains uncertain. This study‐level meta‐analysis investigated the functional outcomes and safety of EVT and best medical management (BMM) compared to BMM alone for treatment of PCA occlusion stroke. Methods: We conducted a literature search in PubMed, Web of Science and Embase for studies in patients with isolated PCA occlusion stroke treated with EVT + BMM or BMM including intravenous thrombolysis. There were no randomized trials and all studies were retrospective. The primary outcome was modified Rankin Scale score of 0–2 at 3 months, while safety outcomes included mortality rate and incidence of symptomatic intracranial hemorrhage (sICH). Results: Twelve studies with a total of 679 patients were included in the meta‐analysis: 338 patients with EVT + BMM and 341 patients receiving BMM alone. Good functional outcome at 3 months was achieved in 58.0% (95% confidence interval [CI] 43.83–70.95) of patients receiving EVT + BMM and 48.1% (95% CI 40.35–55.92) of patients who received BMM alone, with respective mortality rates of 12.6% (95% CI 7.30–20.93) and 12.3% (95% CI 8.64–17.33). sICH occurred in 4.2% (95% CI 2.47–7.03) of patients treated with EVT + BMM and 3.2% (95% CI 1.75–5.92) of patients treated with BMM alone. Comparative analyses were performed on studies that included both treatments and these demonstrated no significant differences. Conclusions: Our results demonstrate that EVT represents a safe treatment for patients with isolated PCA occlusion stroke. There were no differences in clinical or safety outcomes between treatments, supporting randomization of future patients into distal vessel occlusion trials. Abstract : This study‐level meta‐analysis represents the largest study to date to systematically review patients with isolated posterior cerebral artery occlusion stroke treated with endovascular therapy (EVT) compared to no EVT in addition to best medical management. The results demonstrate that EVT represents a safe treatment option for these patients. We found no significant differences in clinical benefit or safety outcomes (mortality rate and incidence of symptomatic intracranial hemorrhage) between the treatments, supporting the randomization of future patients into clinical trials to answer the question regarding the efficacy of EVT in this patient population.